Activate your Learners! Active learning strategies for fostering participant engagement in information literacy sessions - Shamchuk, Lisa; Plouffe, Leah; Nelson, Jody (My University, 2013)
MacEwan University Librarians have revamped introductory information literacy programming to incorporate active learning activities. Our session will discuss the value of active learning, share the chart used to match activities with learning objectives, and allow participants to experience active learning activities that could be adapted for programming in all types of libraries.
Presented on May 30, 2013 at the Canadian Library Association (CLA) Conference in Winnipeg, MB.
Keywords: information literacy; active learning